Catalytic effect of nano additives on decomposition and combustion of RDX-, HMX-, and AP-based energetic composition - Yan, Qi Long; Zhao, Feng Qi; Kuo, Kenneth K.; Zhang, Xiao Hong; Zeman, Svatopluk; DeLuca, Luigi T. (My University, 2016)
The RDX, HMX, and AP are currently the most widely used energetic ingredients in composite solid propellants, since the newly developed energetic compounds are still unable to replace them due to various bottleneck technical problems. In order to improve their combustion efficiency and performance, a common alternative way is to utilize novel nano-sized energetic additives. There are a great many nanomaterials that have been developed in the past decades, which include nanometal particles, metal oxides, metal salts, metallic composites, organometallic compounds, energetic nanocatalysts, and carbon nanomaterials. These additives could increase both the decomposition and the burning rate as well as enhance the combustion efficiency of the corresponding solid propellants by changing the thermal conductivity, energy barrier of thermolysis, heat of reaction, and gas-phase reaction mechanisms of the main ingredients such as RDX, HMX, and AP. This review paper discusses and summarizes the effects of abovementioned nano additives on decomposition kinetics, reaction models, decomposition mechanisms and burning rates, pressure exponents, combustionwave structures, and flame propagation of RDX-, HMX-, and AP-based energetic compositions. The catalytic mechanisms associated with different types of nanomaterials are explained and clarified. Owing to their extremely large specific surface areas, nano-sized energetic additives have significant catalytic effects in both condensed and gas phases during decomposition and subsequent combustion via activation of the reactants and acceleration of their transition state formations. The flame structures of AP-based composite propellants under the effect of some nanoadditives are presented showing the enhanced burning characteristics and stabilized combustion process.
Katalytický efekt nano-přísad na rozklad a hoření energetických kompozitů na bázi RDX, HMX a AP
Keywords: Propellants; Nitramines; Ammonium perchlorate; Burning rate; Flame structure; propelenty; nitraminy; chloristan amonný; rychlost hoření; struktura plamene